2022
DOI: 10.1016/j.talanta.2021.122916
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Covid-19 infected pregnant women sera using laboratory indexes, vibrational spectroscopy, and machine learning classifications

Abstract: Herein, we show differences in blood serum of asymptomatic and symptomatic pregnant women infected with COVID-19 and correlate them with laboratory indexes, ATR FTIR and multivariate machine learning methods. We collected the sera of COVID-19 diagnosed pregnant women, in the second trimester (n = 12), third-trimester (n = 7), and second-trimester with severe symptoms (n = 7) compared to the healthy pregnant (n = 11) women, which makes a total of 37 participants. To assign the accuracy of FTIR spectra regions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…All spectra were analyzed using OPUS 7.0 software. For each spectrum, the baseline correction, vector normalization and smoothing with Savitzky–Golay filter were performed [20] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All spectra were analyzed using OPUS 7.0 software. For each spectrum, the baseline correction, vector normalization and smoothing with Savitzky–Golay filter were performed [20] .…”
Section: Methodsmentioning
confidence: 99%
“…Khan et al showed that Raman spectroscopy analysis of blood serum can distinguish (with 97% of precision, 100% of sensitivity and 95% of specificity) between a healthy patient and a patient infected by hepatitis B virus [19] . Furthermore, in the other work, the authors showed, that using FTIR spectroscopy it is possible to distinguish between females suffering from symptomatic and asymptomatic COVID-19 [20] . In the other work, machine learning methods showed, that using FTIR data it is possible to detect COVID-19 infection with 87% of sensitivity [21] .…”
Section: Introductionmentioning
confidence: 98%
“…Guleken et al studied the detection of COVID‐19 disease in the blood serum of symptomatic and asymptomatic and pregnant women. The samples from pregnant women with COVID‐19 disease and healthy pregnant women were compared [ 23 ]. The samples were analyzed using FTIR; the peak shifts were analyzed with multivariate machine learning approaches (eg, a Random Forest algorithm, a C5.0 single decision tree algorithm, and a deep neural network).…”
Section: Molecular Spectroscopic Techniquesmentioning
confidence: 99%
“…The biochemical levels, peripheral blood cell levels, and coagulation parameters for pregnant women are shown in Figure 2 . The machine learning techniques were able to differentiate among the groups using amide II vibrations, amide I vibrations, and CH 2 scissoring; an accuracy greater than 90% was demonstrated using this approach [ 23 ].…”
Section: Molecular Spectroscopic Techniquesmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Understanding the physiological changes in the cardiopulmonary and immunological systems that occur in pregnancy, ongoing research has shown the higher prevalence of severe SARS-CoV-2 infection among pregnant women. 20,21 With this in mind we hypothesized that pregnant and non-pregnant women would have different clinical variables predictive of a positive COVID-19 test.…”
Section: Introductionmentioning
confidence: 99%